Misconceptions Profile of Riyadul Mubarok Integrated High School Students on Renewable Energy Materials - Quroh, Maya Ainul; Patonah, Siti; Susatyo Nugroho, Ari; Nuroso, Harto (Physics Education Research Journal, 2025)
This research aims to determine (1) whether or not there are misconceptions of class X Riyadul Mubarok Integrated High School students regarding renewable energy application of the Certainty of Response Index (CRI) technique; (2) what sub-concepts are the most common misconceptions experienced by class X students at Riyadul Mubarok Integrated High School regarding renewable energy material using the CRI method. Using the purposive sampling technique, twenty students from class X made up the sample. The phenomena of misunderstandings regarding renewable energy, which contains three subconcepts the the energy conservation law, energy conversion, and the topic of this form of descriptive qualitative research is alternative energy. According to the study's findings, students' misconceptions on renewable energy fall into the low category 19.34%, whereas the sub-concept of energy conversion has the highest number of misconceptions 31.7%. With a value of 14.45%, the alternative energy sub-chapter has the lowest misperception category.The questions with the highest percentage of misconceptions 40% are found in items 4 and 13, whereas question number 9 has the lowest rate of misconceptions 0%. Overall, comprehension of the material on renewable energy is not very high, 25.34% of students understood the concept, compared to a higher number of 37.67% of students who did not